Shaer yang di-Pertuan: Tinjuan Historis Relasi Umara dan Ulama di Brunei Darussalam - bin Kamis, Izzah Naqibah; bin Haji Masri, Muhammed Sahrin (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2020)
Umara and Ulama are two groups who are very influential and has very basic relationships on the State of Brunei Darussalam's growth. Basically, Ulama are known as someone who inherits Anbiya's character, they play a role as murshid in Malay society. This phenomenon has been explained by the importance of their names in some rare materials such as manuscripts, stones and artifacts, hikayat and so on. But The Ulama rarely present it as a poetic/syair approach. The work of